ANALOG CIRCUITS ANALYSIS DIFFERENTIAL METHOD - V. L. Svirid (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Effective (differential) method of analysis of nearly all possible circuit derivations of analog devices, provided as generalized equivalent circuits for alternating or direct (slowly changing) current, which allow to use real differential parameters of active elements with considering their transformation depending on the circuit configuration and the type of the feedback was offered.